Protective Effect of a Formulation Containing Pistacia atlantica Oleo-Gum-Resin and Honey on Experimental Model of Acetic Acid-Induced Colitis in Rats - Pardis Gharazi; Saideh Momtaz; Zahra Rezaei; Mahban Rahimifard; Maryam Baeeri; Alireza Abdollahi; Mohammad Abdollahi; Kimia Zare; Mohammad Hosein Farzaei; Amir Hossein Abdolghaffari* (Iranian Society of Pharmacognosy, 2021)
Background and objectives: Inflammatory bowel disease (IBD) is a recurrent chronic inflammatory disease of the gastrointestinal tract. In Iranian traditional medicine, the oleo-gum-resin of the genus Pistacia is recommended for treatment of various diseases including gastrointestinal disorders. The present study investigated the therapeutic action of a combination of Pistacia atlantica subspecies kurdica oleo-gum-resin and honey in acetic acid-induced colitis in rats. Methods:  Pistacia atlantica oleo-gum-resin was mixed with honey. The mixture was suspended in distilled water. Following induction of colitis with 4% acetic acid in all animals, except in sham group,themixture was orally administered for two consecutive days at the concentrations of 100, 200, 400 mg/kg. Other groups included the control, sham and a standard group (dexamethasone). Microscopic and histopathologic examinations were conducted in inflamed colonic tissue. The inflammatory biomarkers of colitis including interleukin 6 (IL-6), tumor necrosis factor (TNF-α), and myeloperoxidase (MPO) and the gene expression level of toll like receptor-4 (TLR-4) were assessed. Results: Pistacia atlantica oleo-gum-resin+ honey induced significant progress in macroscopic and microscopic scores. Colonic levels of MPO, IL-6, and TNF-α significantly declined in rats treated with the mixture; while significant decrease in mucosal gene expression of TLR-4 and significant improvement of colitis were observed. Pistacia atlantica oleo-gum-resin (400 mg/kg) + honey (400 mg/kg)reduced inflammation of the bowel and colonic ulcer severity shown by downregulation of inflammation cytokines, reduction of neutrophil infiltration, and suppression of TLR-4 expression. Conclusion: The combination might be a promising supplement for treatment of inflammatory disorders.